2010
DOI: 10.1111/j.1365-2605.2009.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obstructive interval and sperm granuloma on patency and pregnancy after vasectomy reversal

Abstract: The objective of this study was to determine the effect of the obstructive interval and the presence of a sperm granuloma on vas patency and pregnancy rate following vasectomy reversal. We identified 334 patients with complete follow-up who met the inclusion criteria. There were significant associations between the obstructive interval and procedure performed as well as with patient age. Patients with longer obstructive intervals were more often older (p < 0.001) and more likely to have a vaseoepididymostomy p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 24 publications
3
22
0
1
Order By: Relevance
“…2). In fact, this finding supports previous observations that sperm counts among patent reversal cases are preserved across all vasectomy obstructive intervals (Magheli et al , 2010a,b). We acknowledge that this does not exclude the possibility that some men can have dramatic impairments to sperm production after vasectomy (as these men may in fact may not have shown patency in this series), but it suggests that the majority of men who have vasectomies do not have impaired sperm output after prolonged obstruction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…2). In fact, this finding supports previous observations that sperm counts among patent reversal cases are preserved across all vasectomy obstructive intervals (Magheli et al , 2010a,b). We acknowledge that this does not exclude the possibility that some men can have dramatic impairments to sperm production after vasectomy (as these men may in fact may not have shown patency in this series), but it suggests that the majority of men who have vasectomies do not have impaired sperm output after prolonged obstruction.…”
Section: Discussionsupporting
confidence: 91%
“…The term vasectomy ‘interval’ used here is identical to vasectomy ‘obstructive interval’ in the literature. For this analysis, and based on published experience, vasectomies of various intervals were arbitrarily divided into two cohorts: ‘younger’ (vasectomy interval 0–15 years) and ‘older’ (vasectomy interval 16 years and higher) (Magheli et al , 2010a). Pregnancy as a separate outcome was not assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, Yang et al followed up 80 patients for more than 2 years following microsurgical two-layer vasovasostomies after different periods of obstructive interval and demonstrated an insignificant difference in the rates of VP at the end of the study [100% (0-8 years), 91% (9-16 years) and 88% ( ‡16 years)] [33]; however, the number of men in each group was not given in these two studies. Furthermore, Magheli et al did not find significant difference in the rates of patency after different obstructive intervals among 242 patients who underwent bilateral microsurgical two-layer vasovasostomies and were followed up for at least 3 months [99% (<5 years, n = 81), 98% (5-10 years, n = 87), 95% (11-15 years, n = 53) and 97% (>15 years, n = 21)], with an overall patency rate of 97% [34]. The procedures were performed by the same experienced surgeons in all studies.…”
Section: Length Of Obstructive Intervalmentioning
confidence: 98%
“…Pregnancy rates, however, decreased dramatically from 85% for obstructive intervals of 15 years or less to 44% for intervals of more than 15 years ( p <0.05) (40). Magheli reviewed a single surgeon's series of 334 vasectomy reversals and reported that patency and pregnancy rates were not influenced by the length of obstructive interval, although multivariate analysis revealed that longer obstructive intervals were associated with an increased tendency to perform VE (41). Kolettis found favorable patency and pregnancy rates in 74 patients with obstructive intervals of 10 years or longer drawn from the experiences of three surgeons.…”
Section: Influential Factorsmentioning
confidence: 99%
“…Age of the female partner significantly impacts postoperative pregnancy rates, as female fertility potential drops profoundly in women over 40 years of age (41,43). Gerrard demonstrated a precipitous decline in postoperative pregnancy rates after age 40 in a series of 249 vasal reconstructions.…”
Section: Influential Factorsmentioning
confidence: 99%